2017
DOI: 10.24034/j25485024.y2014.v18.i4.2179
|View full text |Cite
|
Sign up to set email alerts
|

Kinerja Aparatur Sipil Negara (Asn) Pemerintah Kota Mataram

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…If employee job satisfaction has been fulfilled, then employee performance will increase which can support the company in achieving maximum benefits, whereas if employee satisfaction has not been fulfilled, then employee performance will be disrupted and will have an impact on the difficulty in achieving maximum benefits as targeted. Research by Afriadi (2018) and research by Kusmaningtyas (2012), the results of the study found that job satisfaction has a significant effect on employee performance.…”
Section: Job Satisfactionmentioning
confidence: 78%
See 1 more Smart Citation
“…If employee job satisfaction has been fulfilled, then employee performance will increase which can support the company in achieving maximum benefits, whereas if employee satisfaction has not been fulfilled, then employee performance will be disrupted and will have an impact on the difficulty in achieving maximum benefits as targeted. Research by Afriadi (2018) and research by Kusmaningtyas (2012), the results of the study found that job satisfaction has a significant effect on employee performance.…”
Section: Job Satisfactionmentioning
confidence: 78%
“…Employee satisfaction and performance are very influential factors; this is based on several previous studies, namely: Afriadi (2018), Kusmaningtyas (2012), Yusniawan and Permana (2018), Damayanti et al (2018), Muhridin et al (2019), Muamar (2017), Sudirman, et al (2017), Juniari, et al (2015) found that job satisfaction has a significant effect on employee performance. Meanwhile, Sediarsih (2017), Abidin (2018), and Ekawati, Semmaila, B. and Suriyanti Mangkona (2019) found that job satisfaction did not have a significant effect on the performance of civil servants.…”
Section: Introductionmentioning
confidence: 92%